2015
DOI: 10.1021/acs.jpcb.5b03874
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Perylenediimide DNA Base Surrogates

Abstract: Perylene-3,4,9,10-tetracarboxylic diimides (PTCDIs) are a well-known class of organic materials. Recently, these molecules have been incorporated within DNA as base surrogates, finding ready applications as probes of DNA structure and function. However, the assembly dynamics and kinetics of PTCDI DNA base surrogates have received little attention to date. Herein, we employ constant temperature molecular dynamics simulations to gain an improved understanding of the assembly of PTCDI dimers and trimers. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(92 reference statements)
1
8
0
Order By: Relevance
“…Based on previous findings for ferrocene-terminated alkanethiols [13,14,[33][34][35] (as well as on our experimental observations for monolayers from P0), electrons are likely transported through the macromolecules' tethers and linkers via a rate-limiting and lossy non-resonant tunneling mechanism. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Furthermore, based on reports of rapid electron hopping rates of > 10 7 s -1 [25] and femtosecond charge transfer times in analogous PTCDI-based ensembles, [41] (as well as our computational observations for P1, P2, P3, and P4), electrons are likely transported through the macromolecules' PTCDIbased substructures via a rapid and nearly lossless resonant tunneling mechanism. [13][14][15][16][17][18] The combination of these two mechanisms accounts for the observation of essentially lengthindependent charge transport for our constructs.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Based on previous findings for ferrocene-terminated alkanethiols [13,14,[33][34][35] (as well as on our experimental observations for monolayers from P0), electrons are likely transported through the macromolecules' tethers and linkers via a rate-limiting and lossy non-resonant tunneling mechanism. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Furthermore, based on reports of rapid electron hopping rates of > 10 7 s -1 [25] and femtosecond charge transfer times in analogous PTCDI-based ensembles, [41] (as well as our computational observations for P1, P2, P3, and P4), electrons are likely transported through the macromolecules' PTCDIbased substructures via a rapid and nearly lossless resonant tunneling mechanism. [13][14][15][16][17][18] The combination of these two mechanisms accounts for the observation of essentially lengthindependent charge transport for our constructs.…”
supporting
confidence: 61%
“…First, we selected perylene-3,4,9,10 tetracarboxylic diimide (PTCDI) as the π-conjugated building block for our constructs due to this molecule's well-known electrochemical properties, a propensity for adapting stacked columnar arrangements, and excellent stability under varied conditions. [20,21] Next, we used standard automated oligonucleotide chemistry techniques, which are compatible with PTCDI derivatives, [22][23][24][25][26][27] to prepare, purify, and characterize thiol and ferrocene-modified macromolecules featuring one, two, three, or four PTCDIs arranged on a phospho-alkane backbone (SI Figures S1 to S16). Notably, our constructs' negativelycharged backbone and solubilizing hexaethylene glycol imide substituents facilitated processing and mitigated intermolecular aggregation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, we selected perylene‐3,4,9,10 tetracarboxylic diimide (PTCDI) as the π‐conjugated building block for our constructs because of this molecule's well‐known electrochemical properties, propensity for adapting stacked columnar arrangements, and excellent stability under various conditions . Next, we used standard automated oligonucleotide synthesis techniques, which are compatible with PTCDI derivatives, to prepare, purify, and characterize thiol‐ and ferrocene‐modified macromolecules featuring one, two, three, or four PTCDIs arranged on a phospho‐alkane backbone (Supporting Information, Figures S1–16). Notably, our constructs’ negatively‐charged backbone and solubilizing hexaethylene glycol imide substituents facilitated processing and mitigated intermolecular aggregation.…”
Section: Figurementioning
confidence: 99%
“…To facilitate the interpretation of our experimental observations, we performed DFT calculations. We first adapted literature protocols and used molecular dynamics (MD) simulations to obtain the lowest free energy (most thermodynamically stable) atomistic conformations for the PTCDI‐based substructures of P1 , P2 , P3 , and P4 (Supporting Information, Figures S25 and S26). The simulations revealed that the constituent PTCDIs of P2 , P3 , and P4 were offset with respect to one another but still featured strong π–π stacking interactions, in agreement with the characteristic changes observed for the constructs’ UV/Vis spectra (Supporting Information, Figures S14–16).…”
Section: Figurementioning
confidence: 99%